Integrated Scheduling of Automated Yard Cranes and Automated Guided Vehicles with Limited Buffer Capacity of Dual-Trolley Quay Cranes in Automated Container Terminals - Doaa Naeem; Amr Eltawil; Junichi Iijima; Mohamed Gheith (Logistics)
Background: The key performance index for the container terminals is the vessel berthing time which is highly affected by the scheduling of the different handling equipment. Proper integrated scheduling of the handling equipment is crucial, especially in automated container terminals, where all the handling equipment is automated and must be coordinated to avoid interference. One of the most challenging problems both scholars and terminal operators face is introducing a proper scheduling plan for different equipment, considering the buffer capacity of dual-trolley quay cranes (QCs) and the limited storage locations of import containers. Methods: A mathematical model is proposed to integrate the scheduling of automated yard cranes and automated guided vehicles (AGVs), considering the limited buffer capacity beneath dual-trolley QCs and the storage allocation of import containers. Results: different instances were solved to evaluate the proposed model’s performance and investigate the impact of using dual-trolley QCs instead of single-trolley QCs, and the impact of using different buffer capacities. Conclusions: The results show that the model provides detailed scheduling and assigning plans for the YCs and AGVs besides allocating import containers. Additionally, the dual-trolley QCs can significantly decrease the completion time and increase AGVs’ utilization compared to the single-trolley QCs.